Analysis of the Management of Old-Age Security Funds at BPJS Ketenagakerjaan and Its Impact on Participant Welfare in the Context of Social Protection - Fernandez, Margareth Chatrin Gladys; Herdi, Henrikus; Patty, Thadeus Fransesco Quelmo; Lewar, Maria Viviana Nurak (International Publisher (YAPENBI), 2026)
This study examines the management of the Old Age Security Fund (Dana Jaminan Hari Tua) at BPJS Ketenagakerjaan and its impact on participants’ welfare within the context of social protection. The purpose of this study is to analyze the fund management mechanism of the Old Age Security Fund, assess its compliance with social protection principles, and identify the impact of the OAS program on participants’ welfare. This Research uses a qualitative approach with a case study method at BPJS Ketenagakerjaan in Sikka Regency. Data collection techniques included in-depth interviews with BPJS Ketenagakerjaan employees and OAS program participants, observation, and document review. Data analysis was conducted descriptively and analytically by linking field findings to public accountability theory and the concept of social protection. The Research results show that OAS funds have been managed in a centralized, transparent, and accountable manner in accordance with the law. The management of OAS funds reflects the principles of social protection through income security guarantees, protection against social risks, and the fulfillment of participant rights. The OAS program has a positive impact on participants’ welfare, including a sense of security, certainty of benefits, and future financial protection. This study strengthens empirical Research on the management of employment social security and offers practical implications for improving BPJS Ketenagakerjaan’s governance and services.